Relationship of Lighting, Floor Type, Ventilation, and House Wall with Tuberculosis Incidence in Mandailing Natal District in 2022 - Murni Noviani Nasution; Nurmaini Nurmaini; Sri Malem Indirawati (Budapest International Research and Critics University, 2022)
The research objective is to analyze relationship of lighting, floor type, ventilation, and house wall with tuberculosis incidence in Mandailing Natal District in 2022. This research is a case control study. The case population in this study were tuberculosis sufferers in Mandailing Natal Regency in 2021 which were divided into the work areas of the highland Community Health Center, namely Hutabargot, Sibanggor Jae, Kayu Laut, and Gunung Baringin. While in the lowlands, namely Panyabungan Jae, Longat, Gunung Tua, and Mompang. The total sample in this study is a minimum of 124 people. The data collection method used primary and secondary data. Data analysis used bivariate analysis.